1993
DOI: 10.1073/pnas.90.21.10270
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and stratum-specific expression of the human involucrin promoter in transgenic mice.

Abstract: Involucrin is a marker of keratinocyte terminal differentiation and is expressed only in the suprabasal layers of stratified squamous epithelium. In a previous study with various cell types in culture, we noted that expression of the putative human involucrin promoter was keratinocyte specific. To determine if this promoter is sufficient to direct expression to the suprabasal cells of stratified squamous epithelia in vivo, we have now generated transgenic mouse lines harboring the involucrin promoter sequences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(122 citation statements)
references
References 41 publications
5
117
0
Order By: Relevance
“…In an earlier study, a 2500-bp fragment of the hINV upstream region was shown to confer tissue-and stratum-specific expression (Figure 1). 14 In this fragment, consensus SP1 and AP1 binding sites are located primarily at the 5' and 3' termini of this region while the central region is devoid of transcription binding sites. 17 A 754-bp fragment was derived from this upstream regulatory region including AP1-5, SP1 and AP1-1 binding sites by deletion of the central BglII (Ϫ2100)/MscI (Ϫ192) 1908-bp fragment.…”
Section: Construction Of Minimal Transcriptional Elements Of Involucrmentioning
confidence: 93%
See 3 more Smart Citations
“…In an earlier study, a 2500-bp fragment of the hINV upstream region was shown to confer tissue-and stratum-specific expression (Figure 1). 14 In this fragment, consensus SP1 and AP1 binding sites are located primarily at the 5' and 3' termini of this region while the central region is devoid of transcription binding sites. 17 A 754-bp fragment was derived from this upstream regulatory region including AP1-5, SP1 and AP1-1 binding sites by deletion of the central BglII (Ϫ2100)/MscI (Ϫ192) 1908-bp fragment.…”
Section: Construction Of Minimal Transcriptional Elements Of Involucrmentioning
confidence: 93%
“…When the 754-bp fragment was used to drive LacZ expression in transgenic mice, tissue-and stratum-specific expression was evident, similar to that observed for the full-length promoter ( Figure 1). 14 …”
Section: Construction Of Minimal Transcriptional Elements Of Involucrmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, Myc activation is sufficient to induce profound hyperplasia and tumorigenesis. 11 Expression of Omomyc was targeted to suprabasal keratinocytes using the human involucrin promoter ( Figure 3A) 11,15 and expression of Omomyc protein in skin in vivo assessed immunohistochemically using a rabbit antiOmomyc antibody raised against the leucine zipper mutated region. This antibody exhibited no significant binding to epidermis of single transgenic inv-c-MycER TAM mice, indicating lack of cross-reaction with Myc-ER TAM .…”
Section: Generation and Characterization Of Inv-omomyc Transgenic Micementioning
confidence: 99%